Computational Study of Complex Formation between Hyaluronan Polymers and Polyarginine Peptides at Various Ratios - Kulik, Natalia; Minofar, Babak; Jugl, Adam; Pekař, Miloslav (American Chemical Society, 2023)
Hyaluronic acid, a naturally occurring carbohydrate biopolymer in human tissues, finds wide application in cosmetics, medicine, and material science. Its anionic properties play a crucial role in its interaction with positively charged macromolecules and ions. Among these macromolecules, positively charged arginine molecules or polyarginine peptides demonstrate potential in drug delivery when complexed with hyaluronan. This study aimed to compare and elucidate the results of both experimental and computational investigations on the interactions between hyaluronic acid polymers and polyarginine peptides. Experimental findings revealed that by varying the length of polyarginine peptides and the molar ratio, it is possible to modulate the size, solubility, and stability of hyaluronan-arginine particles. To further explore these interactions, molecular dynamics simulations were conducted to model the complexes formed between hyaluronic acid polymers and arginine peptides. The simulations are considered in different molar ratios and lengths of polyarginine peptides. By analysis of the data, we successfully determined the shape and size of the resulting complexes. Additionally, we identified the primary driving forces behind complex formation and explained the observed variations in peptide interactions with hyaluronan.

Hyaluronic acid, a naturally occurring carbohydrate biopolymer in human tissues, finds wide application in cosmetics, medicine, and material science. Its anionic properties play a crucial role in its interaction with positively charged macromolecules and ions. Among these macromolecules, positively charged arginine molecules or polyarginine peptides demonstrate potential in drug delivery when complexed with hyaluronan. This study aimed to compare and elucidate the results of both experimental and computational investigations on the interactions between hyaluronic acid polymers and polyarginine peptides. Experimental findings revealed that by varying the length of polyarginine peptides and the molar ratio, it is possible to modulate the size, solubility, and stability of hyaluronan-arginine particles. To further explore these interactions, molecular dynamics simulations were conducted to model the complexes formed between hyaluronic acid polymers and arginine peptides. The simulations are considered in different molar ratios and lengths of polyarginine peptides. By analysis of the data, we successfully determined the shape and size of the resulting complexes. Additionally, we identified the primary driving forces behind complex formation and explained the observed variations in peptide interactions with hyaluronan.
Computational Study of Complex Formation between Hyaluronan Polymers and Polyarginine Peptides at Various Ratios
Keywords: Free energy; Molecular mechanics; Molecules; Peptides and proteins; Polymers; Free energy; Molecular mechanics; Molecules; Peptides and proteins; Polymers